Respuesta :
The Remainder Theorem tells us to use the x value of the factor and sub it in for x in our polynomial and what we get in the end is the remainder we would get if we did the synthetic division on it or long division. P(-4)=2(-4)^2+5(-4)-12 is P(-4) = 32 - 20 - 12, and P(-4) = 0. That means when we divide the polynomial by x + 4, we do not get a remainder and the root x = -4 is a factor of the polynomial.
The remainder of dividing 2x² + 5x – 12 by x + 4 is 0
How to determine the remainder?
The given parameters are:
- Dividend = 2x² + 5x – 12
- Divisor = x + 4
Set the divisor to 0
x + 4 = 0
Solve for x
x = -4
Substitute x = -4 in the dividend to calculate the remainder
Remainder = 2(-4)² + 5(-4) - 12
Evaluate
Remainder = 0
Hence, the remainder of dividing 2x² + 5x – 12 by x + 4 is 0
Read more about remainder theorem at:
https://brainly.com/question/13328536
#SPJ2